2005
DOI: 10.1149/1.1831211
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of Polypyrrole at Iron from 1-Butyl-3-methylimidazolium Hexafluorophosphate

Abstract: The ionic liquid, 1-butyl-3-methylimidazolium hexafluorophosphate, was used to deposit adherent and highly conducting polypyrrole coatings at pure iron using a simple potentiostatic technique. Adherent and highly conducting polypyrrole films were formed at the iron substrate using potentials in the range from 1.0 to 1.4 V and with pyrrole concentrations between 0.1 and 0.3 mol dmϪ3 . An increase in the applied potential, or the concentration of the monomer, gave rise to an increase in the rate of polymer growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…Thus, at polymerization potentials some of the metals and their alloys, whether forms passive nonconductive layer (e.g., Zn) [56] or are dissolved in the solution used in the polymerization set up (iron, steel, etc.) [57][58][59]. Usually used substrates for polymer deposition are electrodes made of graphite, carbon fibers, glassy carbon, Indium-tin oxide (ITO), inert metals like Au and Pt [11,43,[60][61][62][63][64][65].…”
Section: Scheme 1 -Electrochemical Polymerization Of Pyrrolementioning
confidence: 99%
“…Thus, at polymerization potentials some of the metals and their alloys, whether forms passive nonconductive layer (e.g., Zn) [56] or are dissolved in the solution used in the polymerization set up (iron, steel, etc.) [57][58][59]. Usually used substrates for polymer deposition are electrodes made of graphite, carbon fibers, glassy carbon, Indium-tin oxide (ITO), inert metals like Au and Pt [11,43,[60][61][62][63][64][65].…”
Section: Scheme 1 -Electrochemical Polymerization Of Pyrrolementioning
confidence: 99%
“…There is also a range of different working electrodes available; existing studies of conducting polymer synthesis in ionic liquids almost entirely use platinum working electrodes, or indium titanium oxide (ITO) glass to allow spectroelectrochemical analysis of the polymer. The synthesis of poly(pyrrole) onto iron has also been studied [29], and a glassy carbon electrode has been used for the deposition of PEDOT [25]. As for all electrochemical techniques, the condition and cleanliness of the electrodes is of great importance; it has been reported that the morphology of poly(pyrrole) films can be greatly altered by inadequate polishing of the working electrode [30].…”
Section: Electrodesmentioning
confidence: 99%
“…However, lower polymer redox currents were observed in the more viscous, less conductive pyrrolidinium ionic liquid compared to the imidazolium species ( 6 ] has also been studied in some detail [29,32,68]. Fenelon and Breslin used this ionic liquid to deposit poly(pyrrole) onto an iron electrode [29], an example of the electrochemical deposition of a conducting polymer from an ionic liquid onto a corrosionsusceptible electrode rather than the inert species used in the other studies.…”
Section: Poly(pyrrole)mentioning
confidence: 99%
See 2 more Smart Citations